In-store attractiveness of national brands and private labels in an emerging market - Araújo, Olegário da Cruz de (2018)
Emerging markets are considered relevant for international manufacturers and retailers to grow their turnovers. In order to achieve their goals, manufacturers and retailers are executing different initiatives to attract new customers such as in-store promotions. However, both in the US and here in Brazil, the results of these actions are questioned. Retailers are also investing in their Private Labels (PLs), which can alter the competitive dynamics within the categories. In the United States and Europe, studies were conducted to assess in-store promotions, impulses and responses in short-term and long-term sales for National Brands (NBs) and also Private Labels (PLs). The research question of this study was to evaluate if in Brazil, an emerging market, the attractiveness of Weighted Distribution, Price and Promotions of National Brands and Private Labels provide similar responses to the impulses. In order to evaluate if the impulses provide long-term residual effects for National Brands (NBs) and Private Labels (PLs), Vectors of Auto Regression (VAR) model was used in a continuous panel of self-service food stores in Greater São Paulo, which is the main metropolitan region of Brazil. The databases by categories (powdered coffee, biscuit, and ready-to-serve fruit juice) contained information of 25 months (November 2013 to November 2015) for each variable (Weighted Distribution, Price and Promotions), by NBs and PLs. The result of this study points out that there is a difference in responses to the impulses (distribution, price, and promotions) between NBs and PLs. National Brands (NBs) showed a greater number of situations with positive residual effects on long-term sales. However, the long-term response on sales occurred only for less than the half of the total potential situations. In other words, more than half of the total potential situations give an absence of statistical significance. The study indicates that there are retailers developing differentiated actions with Private Labels and obtaining, in their sales, positive long-term residual effects. Although modestly, this study contributes to the retail literature by using an econometric model (VAR) to analyze the impulse in some in-store attractiveness variables their long-term sales response to NBs and PLs in an emerging market. In short, the main contribution from the observations of the analyzed categories is that it is possible to Private Label compete without price sensibility and also positioning PL above the average price of the category/segment. The results also suggest that there is an opportunity to review the modus operandi of in-store promotion to get better results.